Creating Dialogue with Parents - Margarita Hamatsu (2010)
In Iceland the importance of parent’s involvement in pre-schools is emphasized in the Pre-school Act and National Curriculum guide for preschool. According to the Icelandic Pre-school Act, one of the principal objectives of pre-school education is to emphasize co-operation with the family. A pre-school director is obliged, by the Pre-school Act and regulation on pre-school activities, to encourage cooperation between homes and pre-schools (Ministry of Education Science and Culture, 2003). Why is it so important that parents need to work with schools and why has it become so important for the policy maker? How do schools actually create relationships with parents? This report intends to answer these questions and aims to present issues, difficulties and achievements on improving parent teacher relations. Aiming to meet the guidelines of the Pre-school Act, Fellaborg pre-school has been active in developing good relations with parents. As a part of the pre-school I wanted my final thesis to to be a part of this development. With the cooperation of the pre-school and close collaboration of ten focused families, it became possible for me to conduct an action research project. Also because the groups of parents are from different backgrounds, this impacted on the development of our starting point.